The Social Role of Religious Institutions in Kurdish Cities in the Century of(4−6AH / 10−12 AD): A Historical-Analytical Study (Raparin Journal of Humanities (RJH), 2026)
Within the field of civilization, cities and urbanization are a lively and vital topic of study. While this has deep historical roots, it continues to hold significant importance in shaping social and cultural life, and thus receives considerable attention in academic and cultural discourse.       As social and socio-economic centers, cities bring together diverse groups and classes of people whose living conditions necessitate the presence of various institutions. Each of these establishments, according to their role and function, impact on the organization of daily life, social relations, and the cultural and economic activities of urban populations. Among them, religious institutions are the most well-known, since they have long been of a great deal of importance in the social life of cities.     Kurdish cities of the 4th and 6th centuries AH (10th and 12th centuries AD), were undoubtedly among the vibrant urban centers within Islamic civilization and their religious institutions, in particular, played a crucial role. This study is devoted to examine the religious institutions and their influence on the degree of social consciousness. The study is organized into two primary sections: the role of religion itself and the influence of religious institutions on social atmosphere. The study includes introduction, conclusion, and bibliography.